Automation of agricultural operations for sustainable rice production in the era of climate change: Automation of farm operations in rice cultivation - Mehta, CR; Senthilkumar, T; Imran, Syed (ORYZA-An International Journal of Rice, 2025)
Rice is a labour-intensive crop and it needs around 850-900 man-h for cultivation of one hectare land. Mechanisation in rice cultivation is getting momentum due to growing labour scarcity and increasing labour wages. The timeliness of farm operations is adversely affected due to labour scarcity during the peak season, thereby reducing the crop yield. To achieve sustainable and environment-friendly rice farming, several sensors based automated technologies have been developed by different ICAR institutes and SAUs for precise application of inputs. This paper gives brief details of the recent developments like remote controlled rice seeder, Unmanned Rice Seeder (URS) with WiFi base wireless communication system, aerial broadcaster for paddy seeds, remote control system for automatic operation of rice transplanters, automatic irrigation system for alternate wetting and drying (AWD) method of irrigation, automatic deep placement fertilizer application system for rice transplanters, variable rate top dressing urea application system etc. There is need to simplify these technologies to rudimentary levels to suit Indian conditions, and make them cost-effective for maximum acceptance by the farming community.